Turnover Intentions in the Creative Education Sector: Empirical Evidence from Music Training Institutes in Bali - Bhaskara, Ni Kadek Adisanti; Suwena, Kadek Rai; Irwansyah, M. Rudi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the turnover intention in the creative education sector, namely music training institutions in Bali. The factors that trigger turnover discussed in this study consist of workload, work stress, and work-family conflict. The research was carried out at one of the non-formal music education institutions in Denpasar City, with a population of 52 employees who are incidentally music teachers, so this study is included in the population research, with multiple linear regression analysis. The results of the study show that simultaneously workload, work stress, and work-family conflict have a positive effect on employee turnover intention at non-formal music education institutions in Denpasar City. This means that the higher the workload, work stress, and work-family conflict simultaneously, the more employee turnover intention will swell. On the other hand, if the workload, work stress, and work-family conflict are low, then employee turnover intention will also decrease.